2018
DOI: 10.1007/s11011-018-0248-9
|View full text |Cite
|
Sign up to set email alerts
|

Oral supplementation of Lanthanum Zirconate nanoparticles moderately affected behavior but drastically disturbed leukocyte count, serum cholesterol levels and antioxidant parameters from vital organs of albino mice in a gender specific manner

Abstract: Lanthanum Zirconate nanoparticles (NPs) are used in blades of gas turbine engines to thermally insulate them and to protect them against hot and corrosive gas streams. However, the information regarding their biocompatibility is limited. The present study was aimed to report the effect of Lanthanum Zirconate NPs on selected aspects of behavior, serum biochemistry, complete blood count and antioxidant parameters from vital organs of albino mice in a gender specific manner. Albino mice, seven weeks old, were ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Nanomaterials are known to induce oxidative stress in living systems by generating reactive oxygen species (ROS), affecting normal gene expression, resulting in a number of disease conditions [ 23 ]. In order to counter this ROS-mediated toxicity, cells have an antioxidant system consisting of enzymes and non-enzyme biomarkers of oxidative stress that try to maintain normal cellular functioning [ 8 , 24 ]. In the present study, a significant increase in brain SOD levels was observed in high-dose nanocomposite-treated male albino mice ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nanomaterials are known to induce oxidative stress in living systems by generating reactive oxygen species (ROS), affecting normal gene expression, resulting in a number of disease conditions [ 23 ]. In order to counter this ROS-mediated toxicity, cells have an antioxidant system consisting of enzymes and non-enzyme biomarkers of oxidative stress that try to maintain normal cellular functioning [ 8 , 24 ]. In the present study, a significant increase in brain SOD levels was observed in high-dose nanocomposite-treated male albino mice ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%